Developing a Flipbook by Utilizing Project-Based Learning (PjBL) to facilitate Independent Curriculum in Primary Schools - Sisca Wulandari; Ilfi Intansari; Lulu Fatihatul Uyun; Nurul Setiani; Elinda Safitri; Taofeek Akolade Gbadeyanka (Universitas Sarjanawiyata Tamansiswa, 2023)
Project-based learning (PjBL) is a recommended learning model for the Independent Curriculum. PjBL prioritizes student activities aimed at generating products through the use of skills such as investigation, analysis, creation, and presentation. These products are based on real-life experiences. In order to enhance kids' excitement for literacy, it is imperative to make PjBL books captivating and groundbreaking. Developing digital-based learning tools, such as flipbooks, is of utmost importance. The research employs the ADDIE methodology, which encompasses analysis, design, development, implementation, and evaluation. The analyzed data include both quantitative and qualitative data. The flipbook based on PjBL to support Independent Curriculum in primary schools was deemed very valid, with a validity value of 93% as assessed by material experts, 95% by media experts, and 93% by teachers, all falling inside the extremely valid category. The individual test, small group test, and field test results demonstrate a high level of validity for the flipbook, with respective percentages of 87%, 95%, and 90%. According on the findings of this assessment, it may be inferred that the product possesses high validity, practicality, and effectiveness. It is appropriate for facilitating Project-based learning (PjBL) and Independent Curriculum in primary school.